Effect of low-intensity microwave electromagnetic radiation on the vital activity of yeast in the presence of graphene - O. M. Lisova; S. M. Makhno; P. P. Gorbyk (Хімія, фізика та технологія поверхні)
To study the influence of graphene (GN) and the low-intensity electromagnetic radiation (LEMP) in the range of 39.5–48.0 GHz on the vital activity of the Saccharomyces cerevisiae yeast, an investigation of the rate of gassing power of yeast suspensions in the concentration of 0.03–0.12 wt. % by means of a volumetric method is reported. Three independent series of experiments were performed: the first one included the dependence of gassing power rates of yeast suspensions on the GN concentrations; the second and third ones were done to research the rates of gassing power in the presence GN and at various LEMR frequencies, where the irradiation procedure was different. It has to be noted that the yeast aqueous suspensions (alone and in the combination with GN) were irradiated in the second series while the yeast in anabiotic state were irradiated afterward the substrate with GN was added in the third series. The respiration intensity of the yeast suspensions was assessed comparing with the blank during each experiment. The vital processes of yeast suspensions are increased by 20-25% compared to the blank in the presence of GN in the suspension, but no change of the gassing power rate behavior (as namely an acceleration or deceleration of lag phase, the change of the curve shape, etc.) in the presence of GN was observed in some cases. The presence of GN in suspensions containing dry yeast is a motivating factor. The initial stage is more sensitive to the presence of GN in the suspension. The activity of the yeast at the final stage is more stable, almost linear and independent on the GN content in the GN concentration range. The value of the relative gassing power rate of the yeast suspensions containing GN is higher than that of blank experiment (about 30%).The mechanism of LEMR influence on microorganisms is under discussion for a long time, there is no common hypothesis concerning the reasons of this phenomenon, as the radiation wavelength significantly exceeds not only the size of the cell organelles, but also the size of the cell. Periodicity of the peaks in the case of yeast may indicate that the resonance phenomenon takes place not due to the actions of the first harmonics but as a result of its higher one. Namely, if the living organisms were exposure to the irradiation with monochromatic LEMR sources in the millimeter range, the resonance effect would not occur. It must be noted that the effect of resonance action can occur in the radio transparent atmosphere ( l= 8–14, 50–100 microns) as radiation passes the waveguides filled with air and the filtration of the signal by the atmosphere components may occur.